Yesterday I was trying to solve this problem on codeforces and found its solution very interesting .. to be honest I had to do alot of research to understand the editorial solution .. so I managed to write a clearer documentation for how to solve these kind of problems.

First of all the problem is that you are trying to maximize f(x,y,z) =

**x^a Y^b Z^c**with the constraint function g(x,y,z) = X+Y+Z = S ..
First of all if (a,b,c) = (0,0,0) then the maximum you get for f(x,y,z) is 1 :) .. otherwise lets solve the problem of at least having one of them > 0.

We can use Lagrange multiplier to solve this problem by doing the following:

=> f(x,y,z) = ƛg(x,y,z) -> Lagrange multiplier

=> x^a . y^b . z^c = ƛ(x+y+z)

**by taking derivative d/dx we get:**

=> ax^(a-1) . y^b . z^c = ƛ(1+0+0) = ƛ ->

**(1)****by taking the derivative d/dy we get:**

=> bx^a . y^(b-1) . z^c = ƛ(0+1+0) = ƛ ->

**(2)****by taking the derivative d/dz we get:**

=> cx^a . y^b . z^(c-1) = ƛ(0+0+1) = ƛ ->

**(3)****This implies the following:**

=> ax^(a-1) . y^b . z^c = bx^a . y^(b-1) . z^c = cx^a . y^b . z^(c-1) = ƛ

=> (1) = (2) = (3)

**By solving (1) and (2) together we get:**

=> ax^(a-1) . y^b . z^c = bx^a . y^(b-1) . z^c = ƛ

=> ax^(a-1) . y^b = bx^a . y^(b-1)

=> bx = ay

=> a/x = b/y ->

**(4)****By solving (2) and (3) we get:**

=> bx^a . y^(b-1) . z^c = cx^a . y^b . z^(c-1)

=> bz = cy

=> c/z = b/y ->

**(5)****From (4) and (5) we get:**

a/x = b/y = c/z ->

**(6)****Now we can use this fact in g(x,y,z) we get:**

=> x+y+z = S

=> x+bx/a+cx/a = S

=> ax+bx+cx = Sa

=> x = Sa/(a+b+c) ->

**(7)****Doing the same for y and z you get:**

=> y = Sb/(a+b+c)

=> z = Sc/(a+b+c)

Now the problem is solved and here is my code:

## No comments:

## Post a Comment